Knowledge domain and evolutionary trends of P2Y receptors in cardiovascular diseases: a bibliometric and altmetric analysis - Yang, Mengyu; Chen, Xuanrui; Lie, Shiyin; Li, Jingjing; Chen, Xuezhang; Chen, Ju; Zhang, Zhiqiang; Lu, Liming; Zeng, Jingchun (Frontiers in Pharmacology, 2026)
ObjectiveThis study employs a dual-metric framework integrating bibliometric and altmetric analyses to systematically map the knowledge domain and structural evolution of P2Y receptor research in cardiovascular diseases (CVDs) from 2005 to 2025.MethodsData were systematically retrieved from the Web of Science Core Collection, Scopus, PMC, and Altmetric databases. By integrating network visualization (CiteSpace, VOSviewer), descriptive bibliometrics, and qualitative content analysis, this study mapped the structural evolution of the research landscape. Additionally, the correlation between scholarly impact and social visibility was quantified using Spearman analysis.ResultsOur analysis encompassed 2,591 articles published between 2005 and 2025, from which the top 100 based on citation count and Altmetric Attention Score (AAS) were selected. The annual publication volume demonstrates sustained growth. The USA contributed 941 articles and holds a leading position, with scholars such as Dominick J. Angiolillo (132 articles) forming a core collaborative network focused on the clinical translation of P2Y12 antagonists. High-impact journals (Impact Factor >5) accounted for 80% of the publications, indicating a strong clinical orientation; the Journal of the American College of Cardiology received the most citations. The research focus has shifted from the antithrombotic mechanisms of early P2Y12 inhibitors like clopidogrel toward immune inflammation, myocardial regeneration, and precision medicine. Altmetric Attention Scores showed a high correlation with social media attention but only a moderate correlation with academic citations, whereas Mendeley readership correlated strongly with citations, revealing a divergence between social visibility and scholarly impact.ConclusionP2Y receptor research has transformed from a singular antithrombotic focus into a multidimensional regulatory network. While P2Y12 antagonists remain clinically dominant, emerging frontiers focus on “de-escalation” strategies, immune-inflammation, and myocardial regeneration. Future progress relies on systematic evaluation of subtype selectivity and novel delivery systems, positioning P2Y receptor modulation as a promising avenue for precision cardiovascular medicine.